CONSIDERING THE PROSPECTS OF PARALLEL IMPORT - V. Kardanov (Вестник университета, 2019)
The issue of parallel import is сomplex. The problem has geopolitical nature. The price of the existing ban is billions of dollars in overpayment for imported goods per year, because of it, the structure of domestic trade in Russia is extremely monopolized: no one can supply goods other than official importers. The article analyzes the typology of import, clarifies the concept of «parallel import», studies the difference between parallel import and counterfeit, etc. It has been concluded, that in Russia parallel import is still in a semi-legal status and efforts should be made to legalize it and establish state control. The movement in this direction was the Resolution No. 8-P / 2018 of the Constitutional Court of the Russian Federation.